Collaborative Observation of Interaction Between Educators and Prospective Educators - Sevita, Ceisya Or’yza; Rahmaningsih, Nanda Eka; Lestari, Vera Dwi; Subekti, Nur Hendra; Setiyawati, Enik (Universitas Muhammadiyah Sidoarjo, 2024)
Collaborative interaction is a collaboration between experienced and aspiring educators to achieve a common educational goal, involving observation and reflection to understand and improve teaching strategies. Research at SD Muhammadiyah 2 Tulangan shows that this collaboration is effective in helping educators and prospective educators develop more effective teaching skills and methods, ultimately improving the quality of education. This research used qualitative methods with interviews, observation and documentation approaches. The aim was to improve collaboration through knowledge sharing and the development of innovative teaching strategies. Socialization of activities included initial meetings, information distribution, discussions and debriefings. Coordination with schools involved scheduling, use of facilities and division of tasks. Learner introductions are conducted so that prospective educators can interact with students. The implementation of collaboration uses active learning methods, with evaluation through data collection, analysis, report preparation, and presentation of results to improve the quality of education. The collaboration involves sharing tasks and responsibilities, as well as guidance from experienced educators, allowing prospective educators to learn classroom management, teaching strategies and how to handle classroom situations. This enhances the professional competence of future educators and enriches the teaching methods of experienced educators through the exchange of ideas. The use of technology and active learning methods also improves learner participation and learning outcomes. The results of this study provide practical guidance for better teacher training programs and more effective education policies, creating a dynamic learning environment, helping all parties develop and improving the overall quality of education.